WORKING PROJECTS AS A SPECIFIC EDUATICATING STRATEGY WITHIN THE BOUNDS OF WORK EDUCATION - BLAZKOVA, Hana (Trends in education, 2009)
The article concem possibilities of fulfilment work project within the bounds of work education in german education, where working project show as one of possible and interesting alternative methods which could be applied in czech education within this bounds of work education.
Keywords: course of study "people and work"; work education; project; work project.